THE INFLUENCE OF ONLINE CUSTOMER REVIEW AND ONLINE CUSTOMER RATING ON PURCHASE DECISIONS THROUGH CONSUMER TRUST IN FORE COFFEE PRODUCTS AT SUN PLAZA MEDAN - Erwin Sahat Mora Pardede; Paham Ginting; Endang Sulistya Rini (CV. Radja Publika, 2023)
This research aims to analyze the phenomenon of the problem in the form of applying different promotions and product tastes at each Fore Coffee outlet causing low consumer purchasing decisions for Fore Coffee products. This is an associative type of research. The population in this research is consumers who have purchased online and offline from Fore Coffee Sun Plaza Medan and the sample is 135 respondents. The sample is withdrawn by a non-probability sampling using the purposive sampling method. The data using are primary data and secondary data are obtained through a list of statements and documentation studies. The data analysis technique employs structural equation modeling (SEM) with the analytical tools of Smart PLS. The research results directly show that online customer reviews and online customer ratings have a positive and significant effect on purchasing decisions, online customer reviews and online customer ratings have a positive and significant effect on consumer confidence, consumer confidence has a positive and significant effect to the purchase decision. Then the test results which are carried out indirectly show that consumers trust are able to mediate online customer review correlation with purchasing decisions and are able to mediate online customer rating correlation with purchase decisions.